2006
DOI: 10.1037/0021-843x.115.4.815
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of facial affect in psychopathic offenders.

Abstract: The authors examined the reliability of facial affect processing deficits found in psychopathic individuals (R. Blair et al., 2004) and whether they could be modified by attentional set. One hundred eleven offenders, classified using the Psychopathy Checklist--Revised (R. Hare, 2003) and Welsh Anxiety Scale (G. Welsh, 1956), performed a facial affect recognition task under 2 conditions. On the basis of research linking psychopathy, amygdala dysfunction, and deficits in facial affect recognition, the authors pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
93
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 26 publications
(37 reference statements)
8
93
2
Order By: Relevance
“…Secondly and in contrast to our expectations, the specific distress emotion (i.e., fear) that has been consistently found to be related to CU traits in prior research [60] was not found. Some research has failed to show a deficit in fear recognition for youths high on CU traits using facial expressions [61,62,63]. Inconsistencies between our findings and those of prior research may be because of differences between samples.…”
Section: Pain Recognition 16contrasting
confidence: 56%
“…Secondly and in contrast to our expectations, the specific distress emotion (i.e., fear) that has been consistently found to be related to CU traits in prior research [60] was not found. Some research has failed to show a deficit in fear recognition for youths high on CU traits using facial expressions [61,62,63]. Inconsistencies between our findings and those of prior research may be because of differences between samples.…”
Section: Pain Recognition 16contrasting
confidence: 56%
“…To accomplish this, prisoners from a secure facility were assessed for psychopathy using the PCL-R, and they were divided into a psychopathic or non-psychopathic group. Using the MacBrain Face Stimulus set, Glass and Newman (2006) expected to find differences in performance between the psychopathic and non-psychopathic group, they found that both groups performed equally as well in identifying facial affect. In light of these findings, the researchers hypothesized that the nature of their task might have affected the outcome.…”
Section: Lack Of Support For Deficits In Facial Affect Recognitionmentioning
confidence: 99%
“…After reviewing the literature, Glass and Newman (2006) conducted an experiment to replicate studies showing specific deficits in sad and fearful affect recognition for 111 Caucasian adult psychopathic individuals with a mean age of 32.30 years. Additionally, the researchers wanted to examine the effect of attentional focus on discerning what facial affect was being displayed.…”
Section: Lack Of Support For Deficits In Facial Affect Recognitionmentioning
confidence: 99%
“…Works on this theme may lead to a greater understanding of these specifi c defi ciencies, given the different types of universal emotions that can be expressed by facial muscles. However, it can also be said that, so far, research in this area has not yielded conclusive data on the true defi ciencies characterizing psychopaths or individuals with traits of psychopathy in terms of understanding other people's emotions, suggesting the need for more specifi cs in this fi eld (Glass & Newman, 2006).…”
mentioning
confidence: 99%
“…The authors, however, did not acquire more signifi cant and specifi c evidence in terms of identifying fear. Glass and Newman (2006), using different task versions for recognizing facial expressions with and without previous clues, did not fi nd specifi c defi ciencies in psychopaths in terms of processing emotional information. According to these authors, the conditions for demonstrating affective defi cits in psychopaths still require more investigations.…”
mentioning
confidence: 99%